Effectiveness of health education as an intervention designed to prevent female genital mutilation/cutting (FGM/C): a systematic review - Susan Waigwa; Lucy Doos; Caroline Bradbury-Jones; Julie Taylor (BMC, 2018)
Abstract Background Female Genital Mutilation/Cutting (FGM/C) is a harmful practice that violates the human rights of women and girls. Despite global efforts to restrict the practice, there have been few reports on major positive changes to the problem. Health education interventions have been successful in preventing various health conditions and promoting service use. They have also been regarded as promising interventions for preventing FGM/C. The objective of this systematic review is to synthesise findings of studies about effectiveness of health education as an intervention to prevent FGM/C. Methods The electronic databases searched were MEDLINE, EMBASE, Cochrane library, Web of Science, Psych INFO, CINAHL and ASSIA. Our search included papers published in the English language without date limits. Study quality was assessed using the Mixed Methods Appraisal Tool (MMAT). A predesigned data recording form was used to extract data from the included studies which were summarised by comparing similar themes. Results Twelve out of 359 individual studies met our inclusion criteria. Seven studies were quantitative, three were qualitative and two used mixed methods. Six studies tested before and after the interventions, four studies assessed the effectiveness of previous interventions used by different research teams and two studies endorsed the intervention. Four main factors emerged and were associated with facilitating or hindering the effectiveness of health education interventions: sociodemographic factors; socioeconomic factors; traditions and beliefs; and intervention strategy, structure and delivery. Conclusions It is vital to target factors associated with facilitating or hindering the effectiveness of health education for FGM/C. This increases the possibility of effective, collective change in behaviour and attitude which leads to the sustainable prevention of FGM/C and ultimately the improved reproductive health and well-being of individuals and communities.